2009
DOI: 10.17221/95/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The dissemination of pelvic limb nerves originating from the lumbosacral plexus in the porcupine (Hystrix cristata)

Abstract: ABSTRACT:In this study the nerves originating from the plexus lumbosacrales of porcupines (Hystrix cristata) were investigated. Four porcupines (two males and two females) were used. The plexus lumbosacrales of animals were appropriately dissected and dissemination of pelvic limb nerves originating from the plexus lumbosacrales was examined. The nerves originated from the plexus lumbosacrales of porcupines (Hystrix cristata): iliohypogastric nerve from T15, ilioinguinal nerve (on the left side of only one anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
26
2
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 9 publications
9
26
2
13
Order By: Relevance
“…Lizardo et al (2009) studied the origin and distribution of the femoral nerve in fetuses of crossbreed zebu cattle and found that the right and left femoral nerves originated from the ventral branches of L4, L5 and L6 in 14 animals (46.7%), from L4 and L5 in 13 cases (43.3%) and L5 and L6 in three cases (10%), similar to that observed in this study in rabbits and to the results obtained by Silva et al in crossbreed sheep concerning the ventral branches, but different in percentage frequencies. Aydin (2009) observed that in the porcupine (Hystrix cristata), the femoral nerve originated mainly from the ventral branches L2 and L3, with contributions from T15 and L1, different from that observed in the present investigation. Cardoso et al (2013) studied the composition of the lumbosacral plexus of the collared anteater (Tamandua tetradactyla) and observed the contribution of lumbar branches (L1-L3) in all studied specimens, and also the participation of T18 in 75% of them in the formation of the femoral nerve.…”
Section: Discussioncontrasting
confidence: 99%
“…Lizardo et al (2009) studied the origin and distribution of the femoral nerve in fetuses of crossbreed zebu cattle and found that the right and left femoral nerves originated from the ventral branches of L4, L5 and L6 in 14 animals (46.7%), from L4 and L5 in 13 cases (43.3%) and L5 and L6 in three cases (10%), similar to that observed in this study in rabbits and to the results obtained by Silva et al in crossbreed sheep concerning the ventral branches, but different in percentage frequencies. Aydin (2009) observed that in the porcupine (Hystrix cristata), the femoral nerve originated mainly from the ventral branches L2 and L3, with contributions from T15 and L1, different from that observed in the present investigation. Cardoso et al (2013) studied the composition of the lumbosacral plexus of the collared anteater (Tamandua tetradactyla) and observed the contribution of lumbar branches (L1-L3) in all studied specimens, and also the participation of T18 in 75% of them in the formation of the femoral nerve.…”
Section: Discussioncontrasting
confidence: 99%
“…No que se refere ao limite cranial do plexo lombossacral, alguns autores incluem os primeiros nervos lombares como integrantes do mesmo, ou seja, os nervos ílio-hipogástrico (cranial e caudal, quando presentes) e ilioinguinal e genitofemoral (Getty, 1986;Aydin, 2009;Castro et al, 2009). Todavia, essa abordagem extrapola o conceito de que somente os nervos lombares caudais estabelecem comunicações para configurar um plexo nervoso, uma vez que os primeiros nervos lombares são formados por ramos solitários (König e Leibich, 2002;Dyce et al, 2010 O plexo lombar recebeu contribuição de T18-L3 em três casos e L1 a S1 em um caso.…”
Section: Resultsunclassified
“…1, 2 e 3) derivou de T18 em dois casos (50%), de T18 e L1 em um caso (25%) e L1 e L2 também em um caso (25%). A participação de nervos torácicos na formação dos nervos do plexo lombar, como observado em 75% dos exemplares deste estudo e em porcos-espinhos (Aydin, 2009), é incomum. Essa diferença se deve provavelmente à menor quantidade de vértebras lombares nessas espécies, sendo três no T. tetradactyla e quatro no Hystrix cristata.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Several studies have investigated the spinal origins of the brachial and lumbosacral plexus which give off nerve branches dispersing to the fore and hind limbs. These include reports on the brachial plexus in dogs (Miller et al, 1964), cats (Getty, 1975), wervet monkeys (Booth, 1991), Chacma baboons (Booth et al, 1997), rabbits (Aslan, 1994;Yilmaz et al, 1995), rats (Green,1968;Chiasson, 1980) and porcupines (Aydin, 2003(Aydin, , 2004; and on the lumbosacral plexus in dogs (Miller et al, 1964;Getty, 1975), rabbits (Barone et al, 1973;McLaughlin and Chiasson, 1987), rats (Green, 1968;Chiasson, 1980;Asato et al, 2000) and porcupines (Aydin, 2009;Aydin et al, 2009). In squirrels, the presence and localization of calbindin-D28k in the kidney and cerebellum (Aydin et al, 2005), the morphology of circulus arteriosus cerebri (Aydin, 2008), the spinal nerves that constitute the plexus lumbosacrales (Aydin, 2010), as well as the arteries originating from the aortic arch (Aydin, 2011), have been studied.…”
mentioning
confidence: 99%